Efficacy of sodium formate as a technological feed additive (preservative) for all animal species. (27th May 2020) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kos Durjava, Mojca; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: In 2015, the EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) issued an opinion on the safety and efficacy of ammonium, calcium and sodium formate when used as a technological additive (preservative) for all animal species. Sodium formate was considered safe for all animal species at a maximum concentration of 10, 000 mg formic acid equivalents/kg complete feed (with the exception of pigs, for which a maximum concentration of 12, 000 mg formic acid equivalents/kg complete feed was considered safe). Sodium formate was also considered safe for the consumer and the environment. The Panel also concluded that sodium formate is non‐irritant to the skin, but mildly irritant to the eyes, and is a respiratory irritant with a potential for sensitisation. The Panel also concluded that 'Sodium formate or solid sodium formate had no discernible effects on microbial numbers in the feed materials examined. The preservative effect of the three formate salts in water for drinking was not demonstrated'. In the current opinion, additional data to demonstrate the efficacy of sodium formate as a preservative in feed for all animal species were assessed. The Panel concluded that sodium formate has the potential to be efficacious as a preservative in feedingstuffs for all animal species at the proposed use level. In the absence of data, the Panel cannot conclude on the efficacy of the use of the additive in water for drinking.